The internationalization of industrial relations in Europe: Prospects and problems - Wolfgang Streeck (Max-Planck-Institut für Gesellschaftsforschung, 1998)
European industrial relations are rapidly internationalizing; internationalization, however, is not necessarily de-nationalization. Even as European integration accelerates, national politics and industrial relations will remain the principal arenas for the social regulation of work and employment in Europe. The paper investigates the implications of European industrial relations developing into a multi-level system within which national regimes compete with each other in an integrated international market. In particular, it tries to outline the emerging new peace formula between business and labor in Europe, which is centered on the notion of joint competitiveness, and its consequences for social protection and the regulation of labor markets. Five examples are given for the continuing importance of national industrial relations in integrated Europe: the renewal of tripartite concertation at national level, especially under the pressure of the Maastricht criteria; the likely impact of European Monetary Union on national collective bargaining regimes; the practical consequences of the European Works Councils Directive of 1994; the experience with the Social Dialogue since the Maastricht Treaty; and the Posted Workers Directive, which is discussed as a possible paradigm of the future relationship between European and national social protection in Europe. – – Die industriellen Beziehungen in Europa internationalisieren sich; Internationalisierung ist jedoch nicht gleichbedeutend mit Entnationalisierung. Trotz beschleunigter europäischer Integration bleiben nationale Politik und nationale Arbeitsbeziehungen die wichtigsten Arenen für die Regulierung der Arbeit in Europa. Das Papier untersucht die Folgen der Transformation der europäischen industriellen Beziehungen zu einem Mehrebenensystem, innerhalb dessen nationale Regime in einem integrierten Markt miteinander konkurrieren. Insbesondere analysiert es die neue europäische Friedensformel zwischen Kapital und Arbeit, die um das Ziel gemeinsamer Wettbewerbsfähigkeit herum organisiert ist, und ihre Konsequenzen für soziale Absicherung und die Regulierung von Arbeitsmärkten. Fünf Beispiele für die anhaltende Bedeutung nationaler industrieller Beziehungen im integrierten Europa werden vorgestellt: die wieder zunehmenden Bemühungen um dreiseitige Konzertierung auf nationaler Ebene, insbesondere unter dem Druck der Maastricht-Kriterien; die wahrscheinlichen Folgen der Europäischen Währungsunion für die nationalen Lohnfindungssysteme; die tatsächlichen Konsequenzen der Direktive über Europäische Betriebsräte aus dem Jahr 1994; die Erfahrungen mit dem Sozialen Dialog seit dem Vertrag von Maastricht; sowie die Entsenderichtlinie, die als mögliches Musterbeispiel für das zukünftige Verhältnis zwischen europäischer und nationaler Sozialpolitik in Europa diskutiert wird.
Keywords: 300